Peran Dinas Sosial dalam Pelayanan Disabilitas di Kabupaten Labuhanbatu - Suhairani Lusri Lubis; Victor Lumbanraja (Yayasan Literasi Sains Indonesia, 2023)
As part of Indonesian citizens, it is appropriate for people with disabilities to receive the rights that should be granted by the State. However, in reality, not all people with disabilities have these rights. This research aims to find out the role of the Labuhanbatu Regency Social Service in providing services to people with disabilities. The technique used for collecting data was conducting field studies, namely by conducting observations, interviews and documentation. Apart from that, literature studies are also carried out, searching for information and reviewing scientific books, newspapers, written works that are related to the problem under study and other literature references. Based on the research that has been carried out, the results of this research show that the services for people with disabilities at the Labuhanbatu Regency Social Service are that the Social Service plays a role in providing services to people with disabilities in Labuhanbatu, the role carried out is in the form of entrepreneurship development, providing basic necessities and also wheelchairs. The obstacles to implementation are the large area, lack of field staff to collect data and lack of budget from the government to provide services.